High Cognitive Activation Strategy Boosts Students' Math Achievement and Self-Efficacy: Strategi Aktivasi Kognitif Tinggi Meningkatkan Prestasi Matematika dan Efikasi Diri Siswa - Hajj, Mustafa Raheem (Universitas Muhammadiyah Sidoarjo, 2024)
General Background: Mathematics education plays a critical role in shaping students' cognitive abilities and self-efficacy. Effective instructional strategies are essential to enhance learning outcomes and foster students' confidence in mathematical problem-solving. Specific Background: Traditional teaching methods often fail to engage students in higher-order thinking, limiting their ability to develop deep mathematical understanding. The